Eros e conoscenza nell’opera di Carla Cerati - Ragonesi, Elisabetta (Il sogno della farfalla, 2019)
In the literary scene of the 1970’s, the photographer and writer Carla Cerati became prominent for her unique research on female identity and extremely modern perspective on the world. Emancipation on one hand and man-woman relationship on the other are the cornerstones laying the groundwork of her research which developed with the aim of finding a possible mediation between women’s professional realization and their fulfilment in love relationships. This article, based on an Italian literature PhD dissertation carried out at the University of Zurich, particularly focuses on the trilogy written by Cerati A woman of our time. The trilogy was published in a second edition in 2005, thirty years after the first publication of the three separate novels which depict the suffered journey of a woman in quest of her own identity. Throughout the three novels, Cerati increasingly and more explicitly investigates the connection between love relationships and identity growth, between Eros and knowledge. After centuries of women’s self-denial and dediction to maternity, the writer illustrates their determination not only in personally choosing for their bodies but also in overcoming the dichotomy, historically considered natural, between body and mind. Drawing from a literary analysis carried out through a psychodynamic perspective, it appears evident how Cerati conceived individual identity as a constantly evolving process which requires fulfilling human relationships in order to become our most truthful self. Looking at the seventies as an historical period characterized by a great conflict between sexes, the emphasis drawn by the author on the importance of establishing an equal man-woman dialectic seems far from obvious and still extremely relevant nowadays.